(untitled) (Journal of Philosophy Culture and Political Science, 2019)
This study is aimed at studying the policy of us economic sanctions against Iran. The topic became relevant again due to Washington’s withdrawal from the Joint comprehensive action plan (JCAP), which was adopted under Iran’s nuclear program. Such a decision by the US implies a new round of economic sanctions against Iran. The withdrawal from the JCAP raises an important question about the effectiveness of the new sanctions, which will be based on more serious pressure. This situation has given rise to fundamental scientific questions, in particular – what is the reason for the effectiveness of sanctions in some cases and failure in others? In this connection, a certain «target country» makes concessions, and others, despite the huge losses from sanctions, persist in the implementation of its strategic course? In our study, we also take into account the existence of other factors, such as: domestic political consensus, alternative trading partners, etc. In our work we use the case-study method, the main source base are legal and regulatory documents that regulate the policy of introduction and implementation of sanctions. Key words: sanctions, Iran, USA, JCAP, sanctions coalition, UN Security Council.